Conventional PCR primers for the detection of grapevine pathogens disseminated by propagating material - Manduláné Farkas, E.; Czotter, N.; Lózsa, R.; Dula, T.; Ember, I.; Várallyay, É.; Szegedi, E. (International Journal of Horticultural Science, 2014)
Polymerase chain reaction driven by sequence specific primers has become the most widely used diagnostic method to detect and identify plant pathogens. The sensitive and cost-effective pathogen detection is exceptionally important in the production of propagating material. In this paper we have collected primer sequence data from the literature for the detection of the most important grapevine pathogens disseminated by propagating stocks by conventional polymerase chain reaction. Basic protocols to obtain template nucleic acids have also been briefly rewieved.